Organization Citizenship Behavior: The Role of Spiritual Leadership, Self Efficacy, Locus of Control and Job Satisfaction - Molana Malik Pandia; Jufrizen Jufrizen; Hazmanan Khair; Hasrudy Tanjung (Jurnal Organisasi dan Manajemen, 2023)
Purpose – This research aimed to investigate and analyze the direct and indirect impact of spiritual leadership, self-efficacy, locus of control, and the job satisfaction of PT. Pelabuhan Indonesia I (Persero) employees on organizational citizenship behavior (OCB). Methodology – This quantitative research was conducted involving data from 61 employees through questionnaires. The data were analyzed using the Structural Equation Model SMART PLS 3.0. Findings – The findings demonstrated that OCB is significantly positively influenced by spiritual leadership, self-efficacy, locus of control, and job satisfaction. Meanwhile, job satisfaction is significantly positively impacted by spiritual leadership, self-efficacy, locus of control, and OCB. This parameter also mediated the relationship between self-efficacy and locus of control with OCB. Originality – This research examined OCB, which has a broad and significant impact on company performance. It also provided better comprehension concerning the relationship of spiritual leadership, self-efficacy, locus of control, and job satisfaction on this indicator.